2021
DOI: 10.1002/agj2.20838
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide enrichment promoted the growth, yield, and light‐use efficiency of lettuce in a plant factory with artificial lighting

Abstract: Lettuce (Latuca sativa L.) is a commercially important crop and a good candidate for production in a plant factory with artificial lighting (PFAL). To explore the influence of CO 2 enrichment (eCO 2 ) on lettuce growth, light-use efficiency (LUE) and various aspects of the growth indicators were specifically assessed. Three CO 2 concentrations ([CO 2 ]): ambient CO 2 (as the control, approximately 400 μmol mol −1 ), approximately double the ambient (DA-CO 2 , 800 ± 50 μmol mol −1 ), and approximately quadruple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
4
5
0
Order By: Relevance
“…Alternatively, it may correspond to the transition of pea plants into the reproductive growth stage (Figure 1). These observations are consistent with the findings of Chen et al [32], where the photosynthetic capacity of lettuce leaves displayed an initial increasing trend during the first 25 days after transplanting, followed by a rapid decline after 5 days. This indicated that the plant was growing poorly during this period and could not improve its growth further at the same level of energy consumption.…”
Section: The Lue Of Pea Shoots Showing An Optimal Response With Plant...supporting
confidence: 93%
See 2 more Smart Citations
“…Alternatively, it may correspond to the transition of pea plants into the reproductive growth stage (Figure 1). These observations are consistent with the findings of Chen et al [32], where the photosynthetic capacity of lettuce leaves displayed an initial increasing trend during the first 25 days after transplanting, followed by a rapid decline after 5 days. This indicated that the plant was growing poorly during this period and could not improve its growth further at the same level of energy consumption.…”
Section: The Lue Of Pea Shoots Showing An Optimal Response With Plant...supporting
confidence: 93%
“…In this study, it was found that light intensity was positively correlated with soluble sugar and vitamin C content in leaves, as well as vitamin C content in stems, among which could significantly increase vitamin C content in leaves (Figure 6). This was similar with the results of Chen et al [32] that light intensity could improve the nutritional value, and the higher light intensity leads to higher levels of vitamin C. However, there was no significant difference in nitrate content in leaves of pea shoots under three levels of light intensity (Figure 4D); nevertheless, light intensity showed a positive correlation with nitrate content in stems of pea shoots. Thus, the conclusion of Voutsinos et al [33] that higher light intensity provides more carbohydrate and photochemical energy to stimulate nitrate assimilation into amino acid in vegetable leaves was not confirmed, but the same as the research results of Maria et al [34], light intensity has no significant effect on nitrate accumulation.…”
Section: Higher Light Intensity Combined With Et-ld Can Improve Yield...supporting
confidence: 91%
See 1 more Smart Citation
“…In this study, it was found that light intensity was positively correlated with soluble sugar and vitamin C content in leaves, as well as vitamin C content in stems, which could significantly increase vitamin C content in leaves (Figure 6). This was similar to the results of Chen et al [31], which showed that light intensity could improve nutritional value and that higher light intensity led to higher levels of vitamin C. However, there was no significant difference in nitrate content in the leaves of pea shoots under three levels of light intensity (Figure 4D). Nevertheless, light intensity showed a positive correlation with nitrate content in the stems of pea shoots.…”
Section: Higher Light Intensity Combined With Et-ld Can Improve Yield...supporting
confidence: 90%
“…Chowdhury et al [33] established five environmental conditions in a plant factory for comparison and discovered the best CO 2 concentration, humidity, and temperature ranges for kale growth and total glucosinolate content, respectively. Chen et al [34] have found that elevated CO 2 concentrations in a PFAL positively influenced lettuce growth, light-use efficiency, and yield, demonstrating the potential of CO 2 enrichment in PFAL systems. Zhiwei T et al [35] investigated the effects of LED lighting arrangement, light source type, and switching intervals on plant growth in artificial light plant factories, aiming to achieve an optimal cultivation strategy.…”
Section: Introductionmentioning
confidence: 99%